Removal of phenol from water using fenchol-menthol hydrophobic deep eutectic solvent - Tan Chee Kee; Ng Yee-Sern; Pang Yean Ling; Hayyan Adeeb (E3S Web of Conferences)
Hydrophobic deep eutectic solvents (HDESs) are regarded as a potential green alternative to conventional organic solvents in separation processes such as liquid-liquid extraction, due to their favourable properties, such as lower vapour pressure and tunable properties. The present work investigated the application of HDES which is synthesised from fenchol and menthol, in the removal of phenol from water. The HDES was synthesised experimentally at a fenchol mole fraction range of 0.1 to 0.9. The experimental results showed that stable liquidus HDES was successfully formed when the fenchol mole fraction in the HDES was 0.2 – 0.9. Further investigation showed that HDES with a fenchol mole fraction of 0.2, which had a low viscosity and high stability in water, had the highest phenol removal efficiency. The phenol removal process was highly sensitive to solution pH and solution-to-HDES ratio. In contrast, phenol removal was less affected by initial concentration and temperature. A high phenol removal efficiency of up to 95.9% was achieved in this study, which further showed the positive feasibility of HDES to serve as an alternative to conventional organic solvents in the liquid-liquid extraction of phenol from water.